The Transitioning of Learners from Zambian Language Literacy to English Literacy in Grade Three in Livingstone District of Zambia: Were teachers prepared to manage it? - Elliot, Machinyise; Pali, Jackline (Shanti Journal, 2023)
The purpose of this study was to establish whether teachers were adequately prepared to transition learners from Zambian language literacy to English literacy in Grade three in Livingstone district. In line with this, it sought to establish the methods the teachers were using in teaching English literacy in Grade three and establish the challenges faced by teachers in managing the transition from Zambian language literacy to English literacy in Grade three. The study employed a mixed method descriptive design which involved both quantitative and qualitative methods. Data was collected using questionnaires, lesson observations, interviews and document analysis. A random selection and a purposive sampling were used to select respondents for the study. The study found that the teachers were not adequately trained during in-set programmers such as workshops, Continuous Professional Developments and TGMs.. Another finding was that the teacher’s attitude to the introduction of English in grade three differed. Some felt that English should be introduced in grade one, while others felt that it should be delayed at least up to grade four or five. Lack of funding at the school level to organize the school inset programs was another issue revealed in the study. it is recommended that the Ministry of Education (MOE) should introduce English literacy courses in colleges, specifically for the transition. It is also recommended that the MOE should provide Grade three English literacy materials and fund in-set programs in schools.